Teratogen and Hematology Effects of Ethanol Extract from Unripe Pisang Kayu (Musa paradisiaca L. var. Kayu) on Mice (Mus musculus) - Nurhayati, Awik Puji Dyah; Abdulgani, Nurlita; Prasetyo, Endry Nugroho; Saadah, Noor Nailis; Shovitri, Maya; Ningsih, Arista Wahyu; Malik, Fajri; Islamiati, Kamila (Trends in Sciences, 2025)
Unripe Pisang Kayu (Musa paradisiaca L. var. Kayu) has been traditionally used in Senduro Village, Lumajang, East Java, as a remedy for diarrhea, with the unripe fruit typically prepared by roasting, steaming or boiling. This traditional use highlights the need to develop it into standardized herbal medicine for broader healthcare applications, necessitating rigorous safety and efficacy evaluations, including preclinical studies. This study aimed to assess the teratogenic and hematological effects of its ethanol extract on female mice (Mus musculus) as part of these evaluations. Mice were administered varying doses (50 - 800 mg/kg BW) of the extract for 14 days, with hematological parameters, including erythrocyte and leukocyte counts, hemoglobin levels and differential leukocyte profiles, measured alongside teratogenicity assessments of fetal length, weight, skeletal structure and organ formation. Observations revealed no significant differences in blood parameters or fetal development between treated and control groups, with no malformations or abnormalities detected. These results suggest that the ethanol extract of unripe Pisang Kayu is non-toxic at tested doses and safe for use, supporting its potential as a standardized herbal antidiarrheal remedy. Further studies, including chronic toxicity and clinical trials, are recommended to ensure its safety and efficacy for human application. HIGHLIGHTS The study found no significant differences in fetal length, weight or organ development between the dose groups (50, 100, 200, 400 and 800 mg/kg BW) and control groups, with 1-way ANOVA analysis (p > 0.05) showing no effect from the extract. Hematological analysis demonstrated no significant impact on erythrocyte, hemoglobin or leukocyte counts on female mice, confirming the extract’s safety for maternal health. This study validates the safety of Pisang Kayu (Musa paradisiaca var. Kayu) extract, demonstrating that it does not cause significant adverse effects on fetal development or maternal health, thereby supporting its potential as a standardized herbal treatment for diarrhea. GRAPHICAL ABSTRACT